The Role of Aisyiyah in Women’s Empowerment in Bandar Lampung City in 1971-2000 - Muntamah, Siti; Basyori, Ahmad; Hasanah, Uswatun; Hamid, Abd Rahman; Setiawan, Agus Mahfudin (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to examine the role of Aisyiyah in women's empowerment in Bandar Lampung City from 1971-2000. The method used in this study is the historical method, which includes the stages of heuristics (source collection), source criticism, interpretation, and historiography. The study results show that Aisyiyah plays an active role in women's empowerment through various programs. In the field of education, Aisyiyah established kindergartens (TK) as part of efforts to educate the younger generation. In the social aspect, this organization initiated the Aisyiyah Foster Children program, the